Strategi Pengembangan Komoditi Karet di Kabupeten Tapanuli Selatan - Nurhafifah, Nurhafifah; Siregar, Edi Batara Mulya; Siregar, Tumpal HS (Universitas Medan Area, 2011)
The rubber is one of the plantation commodity which is the source of livelihood for 1.6 million peasant families, as well as the second largest source of foreign exchange after palm oil and also employers as well as suppliers of various raw materials in the domestic rubber industry. As a commodity plantation, in the development, are required to contribute to optimal results both for the welfare of the community and the sustainability of its business . The objectives of this study are: to determine the external and internal strategic factors that influence the development of smallholder rubber agribusiness in South Tapanuli, to determining the strategic formulation of smallholder rubber development of agribusiness in South Tapanuli, and construct the strategic priority to develop agribusiness in smallholder rubber South Tapanuli .From the analysis, can be conclusions that: there were 13 external strategic factors and 10 internal strategic factors affecting the development of smallholder rubber agribusiness in South Tapanuli. The results of analysis by the SWOT matrix and QSPM analysis can be recommended six priority smallholder rubber agribusiness development strategy and medium term and six long-term strategic priorities to be diimplemerrtasikan by policy makers to agribusiness development of smallholder rubber in South Tapanuli . Keywords : rubber, SWOT and QSPM, agribusiness